(untitled) (Bangladesh Pharmaceutical Journal, 2015)
In the present study, chitin was isolated from the shells of freshwater crab (Sartoriana spinigera), available in Bangladesh. The isolated chitin was converted into chtiosan by deacetylation reaction. The chtiosan was characterized by FT-IR and 1H-NMR spectral analyses. The prepared chitosan was reacted with glutaradehyde, vanillin and salicylaldehyde to synthesize chitosan Schiff bases- vanillin-chitosan, salicylaldehyde-chitosan and glutaradehyde-chitosan. Iron (II) adsorption behavior of these derivatives was studied under varying experimental conditions such as contact time and initial concentration of iron (II) solution. The equilibrium adsorption data were fitted to Freundlich and Langmuir adsorption isotherm models and the model parameters were evaluated. Both the models represented the experimental data satisfactorily. Maximum adsorption capacity for iron (II) ions on chitosan, vanillin-chitosan, salicylaldehyde-chitosan and glutaradehyde-chitosan was evaluated and found be to 68.03, 35.59, 7.50 and 4.78 mg/g, respectively. The uses of chitosan derivatives as environment friendly biosorbents in pharmaceutical and API industries have been hightlighted. DOI: http://dx.doi.org/10.3329/bpj.v17i2.22340 Bangladesh Pharmaceutical Journal 17(2): 193-201, 2014